Disparities in Chronic Pain Experience and Treatment History Among Persons With Traumatic Brain Injury: A Traumatic Brain Injury Model Systems Study. Issue 2 (March 2023) - Sander, Angelle M.; Williams, Michael; Loyo, Karina; Leon-Novelo, Luis; Ngan, Esther; Neumann, Dawn; Agtarap, Stephanie; Martin, Aaron M.; Hoffman, Jeanne; Christensen, Kelsey; Hanks, Robin; Hammond, Flora M.
Abstract : Objective: To determine disparities in pain severity, pain interference, and history of pain treatment for non-Hispanic Whites, non-Hispanic Blacks, and Hispanics with traumatic brain injury (TBI) and chronic pain. Setting: Community following discharge from inpatient rehabilitation. Participants: A total of 621 individuals with medically documented moderate to severe TBI who had received acute trauma care and inpatient rehabilitation (440 non-Hispanic Whites, 111 non-Hispanic Blacks, and 70 Hispanics). Design: A multicenter, cross-sectional, survey study. Main Measures: Brief Pain Inventory; receipt of opioid prescription; receipt of nonpharmacologic pain treatments; and receipt of comprehensive interdisciplinary pain rehabilitation. Results: After controlling for relevant sociodemographic variables, non-Hispanic Blacks reported greater pain severity and greater pain interference relative to non-Hispanic Whites. Race/ethnicity interacted with age, such that the differences between Whites and Blacks were greater for older participants (for severity and interference) and for those with less than a high school education (for interference). There were no differences found between the racial/ethnic groups in the odds of having ever received pain treatment. Conclusions: Among individuals with TBI who report chronic pain, non-Hispanic Blacks may be more vulnerable to difficulties managing pain severity and to interference of pain in activities and mood. Systemic biases experienced by many Black individuals with regard to social determinants of health must be considered in a holistic approach to assessing and treating chronic pain in individuals with TBI.